Kierkegaard on the Problems of Pure Irony - Frazier, Brad (Journal of religious ethics, 2004)
Søren Kierkegaard's thesis, The Concept of Irony, contains an interesting critique of pure irony. Kierkegaard's critique turns on two main claims: (a) pure irony is an incoherent and thus, unrealizable stance; (b) the pursuit of pure irony is morally enervating, psychologically destructive, and culminates in bondage to moods. In this essay, first I attempt to clarify Kierkegaard's understanding of pure irony as “infinite absolute negativity.” Then I set forth his multilayered critique of pure irony. Finally, I consider briefly a distinctly theological component in Kierkegaard's critique. I argue that this feature of Kierkegaard's account can and should be distinguished from the broadly ethical critique of pure irony that I sketch in the second section, even if these components of Kierkegaard's position are found together as a unified whole in The Concept of Irony. My overall goal in this essay is to reveal the subtlety and plausibility of Kierkegaard's critique of pure irony. I also attempt to disclose the richness of the Hegelian account of ethical life to which Kierkegaard recurs in his thesis.